Environmental Assessment of Motorcycle using a Life-Cycle Perspective - Bertha Maya Sopha; Setiowati Setiowati; Sholeh Ma’mun (Indonesian Journal of Life Cycle Assessment and Sustainability, 2017)
Transportation sector contributes as the second largest polluter of the air pollution in Indonesia. Of the transportation sector, road transport has generated 70% of the air pollution, 81% of which is attributable to motorcycles. The motorcycles are currently accounting for 79% of the total motor vehicles. It is predicted that the number of motorcycles will continue to grow at an annual rate of 9-26%. However, due to little attention to the motorcycle’s environmental impacts, this present study, therefore, aims to assess and report the environmental impacts of using motorcycles based on life-cycle perspective. Using a functional unit of one passenger per kilometer (pkm), resource consumption and emissions through the entire life-cycle of a motorcycle were estimated. The foreground Life Cycle Inventory (LCI) was compiled through observation, interview, and secondary data, while the background LCI was based on ecoinvent data v.2.0. Results show that the environmental impacts of the chosen function unit constitute Abiotic Resource Depletion Potential (ADP) of 0.515 g Sb-eq., Global Warming Potential (GWP) of 176 g CO2-eq, Human Toxicity Potential (HTP) of 1.1 g 1.4-DCB-eq, and Acidification Potential (AP) of 0.544 g SO2-eq, respectively. Operation (usage stage) of the motorcycle has been the most contributor to GWP and AP, while manufacturing stage has been the most contributor to HTP. Potential interventions related to the manufacturing process, fuel, and usage of the motorcycle to reduce the environmental impacts are also discussed.